Study into the resonator structures with microprobe sensing elements - Bondarenko, Igor; Borodin, Alexander; Vasilyev, Yuriy; Karnaushenko, Vladimir (Eastern-European Journal of Enterprise Technologies, 2018)
By using methods of mathematical modeling and in the course of an experimental study we have investigated various types of microwave resonator measuring transducers with microprobe sensing elements of coaxial type. Such a study was necessitated by their widespread application for local non-destructive testing and for diagnostics electrophysical characteristics of micro- and nanoscale objects and structures. In order to analyze the resonator measuring transducers with microprobe elements, we have chosen, as the basic criterion, attaining the maximal quality factor, which determines the sensitivity of measurements. We have investigated the structures of measuring transducers based on a coaxial resonator with gradually changing geometrical dimensions, resonators based on the segments of regular waveguides, a cylindrical resonator. In addition, the microwave measuring transducers based on hybrid irregular volumetric and planar structures have been examined. We have considered the distribution character of an electromagnetic field in the structures of transducers, the amplitude-frequency characteristics, as well as changes in them during interaction with external objects. The result of this study is the identified possibilities to improve quality factor for different types of the resonator measuring transducers with microprobe elements to the magnitudes the order of 104. We have proposed, designed, and examined practical structures of measuring transducers, which could be used both in scanning microwave microscopy and in other measuring systems and complexes. We have developed and investigated a measuring transducer based on a coaxial structure that has resonances in a wide range of working frequencies. We have designed and explored the technologically simple structures of high-quality resonator transducers of the pass-through type in the centimeter and millimeter wavelength range based on segments of regular waveguides. A possibility to construct a high-quality measuring transducer based on the hybrid irregular structures, which are excited at the highest types of oscillations, has been experimentally proven. We have revealed a strong influence of characteristics of the coupling elements on the parameters of resonator measuring transducers, which must be taken into consideration when they are applied in practice. The results of our study would make it possible to expand the range and scope of application of methods for the local non-destructive microwave diagnostics of small-dimensional objects and structures